Methanol as a carrier of hydrogen and carbon in fossil-free production of direct reduced iron. (September 2020) - Andersson, Joakim; Krüger, Andries; Grönkvist, Stefan
Highlights: Integration of methanol storage, co-electrolysis, and oxy-fuel combustion. Process may reduce electricity demand of fossil-free hydrogen steelmaking by 25%. Co-electrolysis lowers electricity demand, enables carburization. Hydrogen storage in methanol may be feasible in fossil-free direct reduction steelmaking. Abstract: Steelmaking is responsible for around 7% of the global emissions of carbon dioxide and new steelmaking processes are necessary to reach international climate targets. As a response to this, steelmaking processes based on the direct reduction of iron ore by hydrogen produced via water electrolysis powered by renewable electricity have been suggested. Here we present a novel variant of hydrogen-based steelmaking incorporating methanol as a hydrogen and carbon carrier together with high-temperature co-electrolysis of water and carbon dioxide and biomass oxy-fuel combustion. The energy and mass balances of the process are analyzed. It is found that this methanol-based direct reduction process may potentially offer a number of process-related advantages over a process based on pure hydrogen, featuring several process integration options. Notably, the electricity and total energy use of the steelmaking process could be reduced by up to 25% and 8% compared to a reference pure-hydrogen process, respectively. The amount of high-temperature (>200 °C) heat that must be supplied to the process could also be reduced by up to approximately 34%, although the demand for medium-temperature heat is substantially increased. Furthermore, the suggested process could allow for the production of high-quality direct reduced iron with appropriate carburization to alleviate downstream processing in an electric arc furnace, which is not the case for a process based on pure hydrogen.